Consumption smoothing and price enhancement motives for grain storage: Empirical perspectives from rural Ethiopia - Wondimagegn Tesfaye; Gebrelibanos Gebremariam (Agricultural and Food Economics, 2020)
Consumption smoothing and temporal price arbitrage are the two main economic motives for grain storage in semi-subsistence economies. Nonetheless, little has been documented on the determinants of households' grain storage behavior. Using a rich panel data from maize producing households in Ethiopia, this paper investigates the determinants of households' decision to store grain for consumption and/or for the market. We found that grain storage is mainly determined by climatic factors, technological innovations, and shocks. Grain storage for consumption and for the markets are not mutually exclusive decisions. While the decisions made by the households to store maize for consumption and for the markets are influenced by a host of similar factors, the effects of climatic factors and infrastructure are found to be heterogeneous.
Keywords: D13; O12; Q12; Q18; 330; Grain storage; Precautionary savings; Consumption smoothing; Temporal arbitrage; Shocks; Ethiopia